Communication Response Of Malaysian Civil Service Servants Toward Vision - S. Bhag Singh, Amerjit Singh (2005)
Communication response (information seeking and processing) is a pertinent concern in the study of public affairs. Guided by Grunig's situational theory of publics, this study was primarily undertaken to determine the levels of communication response of Malaysian civil servants towards Vision 2020. The Malaysian civil servants comprised of both management and professional, and support service group. Systematic random sampling technique was employed in the sample selection of the respondents in this study. A self-administered questionnaire was designed as a research instrument. A total of 41 0 respondents participated in the survey conducted in the Federal Territory of Putrajaya and Kuala Lurnpur. The return response rate was 93.8 percent. Statistical techniques engaged included univariate, bivariate and factor analysis, t-test, Pearson Product-Moment Correlation, and Multiple Regression using the enter method. The study revealed that Malaysian civil servants exhibited an active information seeking behavior and a passive information processing behavior towards Vision 2020 issues. In information seeking behavior, actively communicating civil servants showed a likelihood for participating in situations related to Vision 2020. In information processing behavior, civil servants processed the information about Vision 2020 randomly. Additionally, the results displayed that civil servants had a poor to average level of understanding and knowledge about Vision 2020. The situational theory of publics states and this study has confirmed that high problem recognition, and moderate constraint recognition increase both active information seeking and passive information processing behavior among civil servants. This study suggests that besides continuous publicity, it is important to regularly conduct seminars and briefings to enhance civil servants understanding and knowledge about Vision 2020. Finally, this study should be replicated to cover wider geographical areas and be supplemented with other related research methodologies in explaining the activeness or passiveness of communication response among the Malaysian civil servants.